A case study of agroforestry practices and challenges in Mt. Merapi risk and hazard prone area of Indonesia - Zuhud Rozaki; Nur Rahmawati; Oki Wijaya; ATIKAH FAJRIYAH MUBAROK; Masateru Senge; Mohd Fauzi Kamarudin (Society for Indonesian Biodiversity, 2021)
Abstract. Rozaki Z, Rahmawati N, Wijaya O, Mubarok AF, Senge M, Kamarudin MF. 2021. A case study of agroforestry practices and challenges in Mt. Merapi risk and hazard-prone area of Indonesia. Biodiversitas 22: 2511-2518. This paper presents a case study of agroforestry (AF) practices and challenges in Mt. Merapi risk and hazard-prone area of Indonesia. AF has been practiced by farmers in Mt. Merapi risk and hazard-prone area from older generation. Each area in Mt. Merapi has different types of AF such as agrisilviculture, silvopasture, and agrosilvopasture. In the village of Glagaharjo, Yogyakarta, this system has been used for land restoration or conservation. 139 AF adopters were chosen from 269 respondents that have been randomly interviewed from four different areas around Mt. Merapi. Statistical descriptive method using values of mean and percentage were used. Additionally, multinomial Logistic regression was utilized to understand the model. The findings of the study show that the trend of AF is increasing, especially in Glagaharjo, after the 2010 eruption. AF systems are also found to be practiced for mitigation strategies in facing Mt. Merapi hazards and risk, especially for crop protection, and land and water conservation. Promoting AF as one of the coping strategies in facing Mt. Merapi hazards and risk is important as indicated by the results of this study.